2018
DOI: 10.1136/bcr-2017-221163
|View full text |Cite
|
Sign up to set email alerts
|

Rogue one: a story of tophaceous gout in the spine

Abstract: A 26-year-old man with history of extensive tophaceous gout presented to the referring facility with decreased bilateral lower extremity sensation and motor function that began acutely 1 week prior to admission and had progressed to urinary incontinence. The patient was admitted to the intensive care unit due to concern for sepsis secondary to epidural abscess. The patient was started on empiric vancomycin and cefepime. Neurosurgery did not recommend acute neurosurgical intervention given the lack of a compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…For example, there have been cases in which spinal gouty tophus was initially diagnosed as tuberculous tenosynovitis or even malignancy due to the heterogeneous, hyperintense morphology of the lesion. 2 , 6 Although lumbar spinal manifestations are the most common, the literature suggests that a tophus arising from vertebral body or disc space, as in this case, is exceedingly rare. 4 , 9 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, there have been cases in which spinal gouty tophus was initially diagnosed as tuberculous tenosynovitis or even malignancy due to the heterogeneous, hyperintense morphology of the lesion. 2 , 6 Although lumbar spinal manifestations are the most common, the literature suggests that a tophus arising from vertebral body or disc space, as in this case, is exceedingly rare. 4 , 9 …”
Section: Discussionmentioning
confidence: 78%
“…Kostman et al 6 reported two cases initially diagnosed as tuberculous tenosynovitis that were later discovered to be gouty tophi when symptoms persisted refractory to antibiotics. Dwarki et al 2 illustrated gouty tophus masked as a malignancy on MRI due to the heterogeneous, hyperintense morphology of the lesion. Other case reports of gout tophus in the spine demonstrate a similar morphology to other intraspinal compressive morphologies with nonspecific overgrowth into surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] As of 2019, only 159 cases of spinal gout have been reported; gout is typically diagnosed in the fourth decade of life, the average age in men 30 years old. [2] Around 50% of patients present with neurological sequela requiring surgery if there is a neurological compromise. Here, our patient required surgical decompression/fusion to both establish the diagnosis and treat the acute paraparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other presentations are rare and include predominant or isolated paraspinous, paravertebral, epidural, and/or foraminal tophi, 12,[18][19][20] involvement of the atlantoaxial joint with subsequent subluxation or cord compression via mass effect, 21,22 and involvement of the filum terminale. 23…”
Section: Other Presentationsmentioning
confidence: 99%